The Impact of Quizizz Learning Media in Increasing Interest and Learning Motivation for Early Childhood Education Students - Nuary, Muhammad Guruh; Abidin, Jenal; Pranatha, Aria; Martiningsih, Tri Wahyu; Rusdiani, Irsad (Journal International of Lingua and Technology, 2024)
As technology advances in the education sector, there are many updates in the use of learning media, one example is using the Quizizz application. The Quizizz application really helps teachers in the teaching and learning process. The Quizizz application has many interesting features, and makes learning more fun. The quizizz application is one of the learning media chosen by teachers to carry out the learning process for early childhood. The aim of this research is to find out how big the impact of quizizz learning media is in increasing early childhood interest and motivation in learning. This research uses a qualitative method where data is obtained through introducing the Quizizz application to young children and direct interviews with several parties such as teachers and parents of children. The research results show that the use of the Quizizz application in early childhood is carried out well starting from the planning, implementation and evaluation stages. From this research, it can be concluded that the Quizzizz application is very helpful in the children's learning process so that children understand the lessons taught by the teacher more quickly and the interesting features can also increase children's learning motivation. The limitation of this research is that the researcher only conducted research on the quizizz application for early childhood even though there are still many applications that can be used to provide learning motivation for early childhood. The researcher hopes that future researchers can conduct research related to early childhood learning motivation but by using other learning media. This research recommends that future researchers use the research as a reference in conducting research on the impact of the Quizizz application in increasing learning motivation in young children.